Non-Linear Contact Finite Element Analysis Of Split Hopkisnon Tensile Bar - Jason, Edwin (Universiti Sains Malaysia, 2022)
To test whether a component’s design can resist impact loading is important. This test is known as high strain rate testing. Split Hopkinson Pressure Bar is used to study the material behaviour at high strain rates. However, there are not much specific guideline to determine the design parameters of a Tensile SHPB. Therefore, a Tensile SHPB is modelled in Abaqus and Ansys to characterize the stresses in the incident bar and using the simulation results to propose a small-scale Tensile SHPB. The analysis simulation is done based on the geometry and material of a Tensile SHPB developed in the Mechanical Engineering laboratory. The finite element analysis was done based on contact mechanic approach. By using the maximum pressure from the pressure tank, the maximum stress experienced by incident bar under frictionless condition is recorded as 677MPa. Subsequently, by taking inconsideration of friction and pressure losses in the simulation the maximum stress of 403.50MPa is experienced by incident bar. The small-scale Tensile SHPB with the same capability were set to fit on 1.8m x1.2m regular table determined by stress strain ratio